2017
DOI: 10.1038/s41598-017-06512-5
|View full text |Cite
|
Sign up to set email alerts
|

Tunable uptake/release mechanism of protein microgel particles in biomimicking environment

Abstract: Microgels are intra-molecular crosslinked macromolecules that can be used as vehicles to deliver and release drugs at the point-of-need in the patient’s body. Here, gelatin microgels were formed from microfluidics droplets, stabilised by aldehydes and frozen into a spheroidal shape. Microgel morphology and response to external stimuli were characterised. It was found that the behaviour of the spheroidal microgels was sensitive to both pH and ionic strength and that the distribution of charges into the microgel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Numerous proteins are used to form gels under specific conditions at microscale allowing the encapsulation of active molecules and their release. Pepe et al (2017) developed gelatin microgels by microfluidic with high sensitive response to pH and ionic strength, controlling their swelling and uptake behavior. These authors used two model compounds (rhodamine B and methylene blue) to analyse the uptake and release mechanism at specific conditions, mimetizing the stomach environment (Pepe et al, 2017).…”
Section: Macro-and Microscale Structuresmentioning
confidence: 99%
“…Numerous proteins are used to form gels under specific conditions at microscale allowing the encapsulation of active molecules and their release. Pepe et al (2017) developed gelatin microgels by microfluidic with high sensitive response to pH and ionic strength, controlling their swelling and uptake behavior. These authors used two model compounds (rhodamine B and methylene blue) to analyse the uptake and release mechanism at specific conditions, mimetizing the stomach environment (Pepe et al, 2017).…”
Section: Macro-and Microscale Structuresmentioning
confidence: 99%
“…In this context, a good loading is achieved, and the drug is released slowly from the carrier system without the active ingredient being adversely affected. Compared to Kataokas approach, microgels could potentially be advantageous for such an application, as their ability to react to external stimuli such as temperature [ 26 ] or pH [ 36 ] can be easily utilized to realize a targeted release of active ingredients with the highest possible precision. One of the most remarkable examples in this context is probably the novel drug cannabidiol (CBD) [ 37 ], which is often applied after being dissolved in olive oil.…”
Section: Introductionmentioning
confidence: 99%
“…32 In other studies, using microfluidics, gelatin cross-linked with glutaraldehyde produced prolate microparticles with length of the longer axis greater than 100 μm. 35 It was reported that lithography allowed manufacturing of spheroids in very broad range of aspect ratios (with long axis 40-fold longer than diameters of native particles). The particles were formed via particle replication in nonwetting templates (denoted as PRINT) followed by their mechanical uniaxial elongation.…”
Section: Introductionmentioning
confidence: 99%